Critical success factors for successful enterprise architecture implementation in bank - Fatemeh, Nikpay (2014)
Enterprise Architecture (EA) is a strategy to align business and Information Technology (IT) of an enterprise for increasing competitiveness. Well implemented EA caused innovation and transformation for enterprise and it leads to stability and flexibility. In EA implementation, Critical Success Factors (CSFs) refer to those factors which effect on success implementation of EA. By utilizing CSFs within EA project, enterprise could be reached their goal better, faster and cheaper. EA implementation project without understanding CSFs leads to inappropriate direction and dissatisfaction of EA project. Banking enterprises which have sensitive and important data have to find an appropriate plan to implement the EA. Since understanding the CSFs provide a better solution and right direction for EA implementation, banking enterprises are looking to find it due to insufficient work related to CSFs of EA particularly in banks. This research aims to propose CSFs Model for having Successful EA Implementation in Bank. The proposed CSFs model include Governance, Top Management Commitment, Technology and Infrastructure, EA team capability and Communication. This research applies quantitative research methodology by means of questionnaire. Selected respondents of questionnaire were 86 people consist of Enterprise Architect, IT managers, IT consultants of eight Malaysian Banks. Statistical analyses were used to evaluate proposed CSFs model and investigate the relationship between proposed CSFs and successful EA implementation. The result shows that all proposed CSFs were significant contribute to the model and Governance is the strongest contribution to explaining successful EA implementation. This research result is informational and useful for Enterprise Architects of banking industry and graduate students considering conducting research on EA and practitioners.